Paparan Dakwah Digital dan Moderasi Beragama di Kalangan Mahasiswa Universitas Kadiri - Ade Ajeng Bela Saputri; Suko Susilo; Titin Widya Risni (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Students university kadiri access religious information digital technology has transformed. This study examines the relationship between exposure to digital da’wah and students’ understanding of religious moderation. Employing a sequential explanatory mixed-methods design, data were gathered from 108 students at University Kadiri (mean age = 20.3; 62% female) through surveys and in-depth interviews with four informants. Measurement validity was ensured using the Rasch Model (exposure: item reliability = 0.92, separation index = 3.41; moderation: reliability = 0.87, separation index = 2.61). Quantitative analysis using Spearman’s rho indicated a moderate positive correlation between social media exposure and religious moderation (ρ = 0.499, 95% CI [0.35, 0.62], p < .001). Qualitative findings revealed that exposure to inclusive and tolerant da’wah content fostered openness, tolerance, and non-violence, while limited or entertainment-focused exposure weakened these values. This study highlights the implications of digital da’wah for higher education, particularly the need to integrate moderation literacy into curricula and encourage strategic use of digital platforms to promote tolerance. Limitations include the single-site sample and the influence of algorithmic bias on content exposure. Future research should adopt multi-site and longitudinal designs to better capture dynamic shifts in digital consumption and its impact on students’ religious perspectives.